The representation of the hybrid in Bosch’s paiting - Pol, Yasmin (2020)
The present work has aims to conceptualize historically the hybrid, highlighting the meanings attributed to it, and relate it to the work of Hieronymus Bosch. For the understanding of these relations, one must understand separately each element, so the article is divided into three parts: the concept of the hybrid, the life and work of Hieronymus Bosch and the analysis of one work by this artist. This brief image analysis makes evident the visions and connotations attributed to the hybrid since Ancient History. As research methodology, scientific books and articles about the topic were used, as well as the inventory and study of Bosch works.